Dual Antiplatelet Therapy for 6 Versus 18 Months After Biodegradable Polymer Drug-Eluting Stent Implantation - Nakamura, Masato; Iijima, Raisuke; Ako, Junya; Shinke, Toshiro; Okada, Hisayuki; Ito, Yoshiaki; Ando, Kenji; Tanaka, Hiroyuki; Takiuchi, Shin; Nishida, Yasunori; Kawaguchi, Katsuhiro; Kadotani, Makoto; et al. (JACC. Cardiovascular interventions, 2017)
The NIPPON (Nobori Dual Antiplatelet Therapy as Appropriate Duration) study was a multicenter randomized investigation of the noninferiority of short-term versus long-term dual antiplatelet therapy (DAPT) in patients with implantation of the Nobori drug-eluting stent (DES) (Terumo, Tokyo, Japan), which has a biodegradable abluminal coating. The optimum duration of DAPT for patients with a biodegradable polymer-coated DES is unclear. The subjects were 3,773 patients with stable or acute coronary syndromes undergoing Nobori stent implantation. They were randomized 1:1 to receive DAPT for 6 or 18 months. The primary endpoint was net adverse clinical and cerebrovascular events (NACCE) (all-cause mortality, myocardial infarction, stroke, and major bleeding) from 6 to 18 months after stenting. Intention-to-treat analysis was performed in 3,307 patients who were followed for at least 6 months. NACCE occurred in 34 patients (2.1%) receiving short-term DAPT and 24 patients (1.5%) receiving long-term DAPT (difference 0.6%, 95% confidence interval [CI]: 1.5 to 0.3). Because the lower limit of the 95% CI was inside the specified margin of −2%, noninferiority of short-term DAPT was confirmed. Mortality was 1.0% with short-term DAPT versus 0.4% with long-term DAPT, whereas myocardial infarction was 0.2% versus 0.1%, and major bleeding was 0.7% versus 0.7%, respectively. The estimated probability of NACCE was lower in the long-term DAPT group (hazard ratio: 1.44, 95% CI: 0.86 to 2.43). Six months of DAPT was not inferior to 18 months of DAPT following implantation of a DES with a biodegradable abluminal coating. However, this result needs to be interpreted with caution given the open-label design and wide noninferiority margin of the present study. (Nobori Dual Antiplatelet Therapy as Appropriate Duration [NIPPON]; NCT01514227) [Display omitted]